Neutrophil–lymphocyte ratio in acute ischemic stroke: Immunopathology, management, and prognosis. (30th June 2021) - Sharma, Divyansh; Spring, Kevin J.; Bhaskar, Sonu Menachem Maimonides
Abstract : There is an ongoing need for accurate prognostic biomarkers in the milieu of acute ischemic stroke (AIS) receiving reperfusion therapy. Neutrophil–lymphocyte ratio (NLR) has been implicated in emergency medicine and acute stroke setting as an important biomarker in the prognosis of patients. However, there are ongoing questions around its accuracy and translation into clinical practice given suboptimal sensitivity and specificity results, as well as varying thresholds and lack of clarity around which NLR time points are most clinically indicative. This article provides a comprehensive overview of the role of NLR in AIS patients receiving reperfusion therapy and perspectives on areas of future research. NLR may be an important biomarker in risk stratifying patients in AIS to identify and select those who are more likely to benefit from reperfusion therapy. Appropriate clinical decision‐making tools and models are required to harness the predictive value of NLR, which could be useful in identifying and monitoring high‐risk patients to guide early treatment and achieve improved outcomes. Our understanding of the role of NLR in the immunopathogenesis of AIS is also suboptimal, which hinders the ability to translate this into clinical practice.